On the development of the electrochemical potentiokinetic method - Acciari, Heloísa A. [UNESP]; Guastaldi, Antonio Carlos [UNESP]; Brett, Christopher M.A (Elsevier, 2001)
The development of electrochemical potentiokinetic methods as applied to the testing of metals and alloys is followed from its early phases up to its latest advances relating to intergranular corrosion, SCC and pitting corrosion tests of stainless steels and special alloys and to the examination of their structure and properties. In assessing the susceptibility to intergranular and pitting corrosion by potentiokinetic polarization tests, the polarization curves which apply to the bulk of the alloy grains (the matrix) must be distinguished from those pertaining to grain boundaries. Cyclic polarization measurements such as the electrochemical potentiokinetic reactivation (EPR) test make it possible to derive the alloy's susceptibility to intergranular, pitting and crevice corrosion from characteristic potentials and other quantities determined in the 'double loop' test. EPR is rapid and responds to the combined effects of a number of factors that influence the properties of materials. The electrochemical p otentiokinetic tests are sensitive enough to detect structural changes in heat treated materials ranging far beyond the stainless steels alone, and can be used for non-destructive testing aimed at elucidating the properties and behavior of materials. © 2001 Elsevier Science Ltd. All rights reserved.
Keywords: EPR test; Intergranular corrosion; Pitting; Stainless steels; Stress corrosion cracking; Grain boundaries; Granular materials; Nondestructive examination; Polarization; Stainless steel; Steel corrosion; Electrochemical potentiokinetic reactivation (EPR) tests; Electrochemistry